2020
DOI: 10.1007/s00262-019-02469-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive activity of Vδ2+ γδ T cells on αβ T cells is licensed by TCR signaling and correlates with signal strength

Abstract: Despite recent progress in the understanding of γδ T cells' roles and functions, their interaction with αβ T cells still remains to be elucidated. In this study, we sought to clarify what precisely endows peripheral Vδ2 + T cells with immunosuppressive function on autologous αβ T cells. We found that negatively freshly isolated Vδ2 + T cells do not exhibit suppressive behavior, even after stimulation with IL-12/IL-18/IL-15 or the sheer contact with butyrophilin-3A1-expressing tumor cell lines (U251 or SK-Mel-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…It was observed that the suppressive activity of activated Vδ2T cells on autologous αβ T cells was dependent on the signal strength of the TCR stimulation and enforced by IL-15, but it was independent of TGF-β (in line with the independence of FOXP3). 114 The molecular mechanism of how γδ T cells suppress their neighbors is not precisely known. Conceivably, suppression might, in some instances, result from direct killing of αβ T cells by activated γδ T cells.…”
Section: γδ T Cells: Regulating and Being Regulatedmentioning
confidence: 99%
“…It was observed that the suppressive activity of activated Vδ2T cells on autologous αβ T cells was dependent on the signal strength of the TCR stimulation and enforced by IL-15, but it was independent of TGF-β (in line with the independence of FOXP3). 114 The molecular mechanism of how γδ T cells suppress their neighbors is not precisely known. Conceivably, suppression might, in some instances, result from direct killing of αβ T cells by activated γδ T cells.…”
Section: γδ T Cells: Regulating and Being Regulatedmentioning
confidence: 99%
“…A more recent approach for cd T cells expansion is using anti-cd TCR mAb (Fisher et al 2014;Dong et al 2018;Schilbach et al 2020). Specific subset of cd T cells can be expanded using Ab against a certain Vc or Vd chain.…”
Section: Role Of CD T Cells In Human Sars-cov-2 Infectionsmentioning
confidence: 99%
“…It has been known for some time that the TCR is involved in the acquisition of suppressive function of γδ T cells [12][13][14] and we showed recently that suppressive activity of Vδ2 + γδ T cells on αβ T cells is licensed by TCR signaling and correlates with signal strength [56]. Thus TCR-independent activation of γδ T cells is highly desirable for unbiased immunotherapy in cancer to prevent unwanted effects on adaptive T cell responses.…”
Section: Discussionmentioning
confidence: 90%